Butterfly oviposition preference is not related to larval performance on a polyploid herb. Issue 9 (20th March 2016) - König, Malin A. E.; Wiklund, Christer; Ehrlén, Johan
Abstract: The preference–performance hypothesis predicts that female insects maximize their fitness by utilizing host plants which are associated with high larval performance. Still, studies with several insect species have failed to find a positive correlation between oviposition preference and larval performance. In the present study, we experimentally investigated the relationship between oviposition preferences and larval performance in the butterfly Anthocharis cardamines . Preferences were assessed using both cage experiments and field data on the proportion of host plant individuals utilized in natural populations. Larval performance was experimentally investigated using larvae descending from 419 oviposition events by 21 females on plants from 51 populations of two ploidy types of the perennial herb Cardamine pratensis . Neither ploidy type nor population identity influenced egg survival or larval development, but increased plant inflorescence size resulted in a larger final larval size. There was no correlation between female oviposition preference and egg survival or larval development under controlled conditions. Moreover, variation in larval performance among populations under controlled conditions was not correlated with the proportion of host plants utilized in the field. Lastly, first instar larvae added to plants rejected for oviposition by butterfly females during the preference experiment performed equally well as larvae growing on plants chosen for oviposition. The lack of a correlation between larval performance and oviposition preference for A. cardamines under both experimental and natural settings suggests that female host choice does not maximize the fitness of the individual offspring. Abstract : The preference–performance hypothesis predicts that female insects maximize their fitness by utilizing host plants which maximize larval performance. Still, an increasing number of studies have failed to find a positive correlation between oviposition preference and larval performance. We show that there is no correlation between larval performances of Anthocharis cardamines and oviposition preferences on the host plant Cardamine pratensis, using larvae descending from 419 oviposition events by 21 females and plants from 51 populations, which indicates that female oviposition behavior and host choice is being selected to maximize the total fitness of the females rather than that of their individual offspring in contradiction with the preference–performance hypothesis.